Detection Rate and Clinical Relevance of Ink Tattooing during Balloon-Assisted Enteroscopy. (5th November 2017) - Römmele, C.; Ebigbo, A.; Schrempf, M.; Messmann, H.; Gölder, S. K.
Abstract : Background and Aims . Balloon-assisted enteroscopy (BAE) is a well-established tool in the diagnosis and therapy of small bowel diseases. Ink tattooing of the small bowel is used to mark pathologic lesions or the depth of small bowel insertion. The purpose of this study was to determine the safety, the detection rate, and the clinical relevance of ink tattooing during BAE. Methods . We performed a retrospective analysis of all 81 patients who received an ink tattooing during BAE between 2010 and 2015. Results . In all patients, ink tattooing was performed with no complications. 26 patients received a capsule endoscopy after BAE. The tattoo could be detected via capsule endoscopy in 19 of these 26 patients. The tattoo of the previous BAE could be detected via opposite BAE in 2 of 11 patients. In 9 patients, ink tattooing influenced the choice of approach for reenteroscopy. In 7 patients, the tattoo was used for intraoperative localization and in 3 patients for intraoperative localization as well as for reenteroscopy. The intraoperative detection rate of the tattoo was 100%. Conclusion . Ink tattooing of the small intestine is a safe endoscopic procedure to mark the depth of scope insertion or a pathologic lesion during balloon-assisted enteroscopy.